Study protocol for a randomized controlled trial of a group-adapted Somatic Experiencing® intervention for Indonesian women survivors of sexual assault with PTSD symptoms - Ligina Ayudia; Fredrick Dermawan Purba; Annemarie Samuels; Aulia Iskandarsyah (PLoS ONE, 2025)
Background Sexual assault affects 35.6% of women globally. In Indonesia, 1 in 3 women aged 15–64 have experienced physical and/or sexual assault. This often leads to post-traumatic stress disorder (PTSD) and related symptoms. The standard PTSD treatments have cultural and resource limitations, which emphasize the need for a culturally adapted intervention. Somatic Experiencing® (SE)®, a body-oriented trauma therapy, has shown promise in reducing PTSD symptoms across diverse populations, but its cultural applicability and effectiveness in Indonesia remain under-investigated. This study addresses that gap by adapting SE®, for Indonesian women survivors of sexual assault. Methods This study is a parallel-group, randomized controlled trial (RCT) designed to assess the effectiveness of a 10-session group-based SE® intervention, compared withcontrol group. A total of 207 participants will be recruited and randomly assigned using a 2:1 allocation ratio (n = 138 intervention, n = 69 control). The intervention consists of structured group activities based on SE® principles, targeting improvements in PTSD symptoms, resilience, and quality of life. Furthermore, participants will be assessed at multiple points using standardized measures (PCL-5, CD-RISC-25, WHOQOL-BREF). Analysis will be conducted using SPSS version 22.0 for quantitative data and thematic coding for qualitative insights. Discussion This study represents the first RCT of culturally adapted SE® intervention in Indonesia. The findings are expected to inform trauma-focused clinical practice in low-resource settings and contribute to the global understanding of body-based therapy effectiveness in diverse cultural contexts. Results may also provide evidence for scalable group interventions targeting PTSD among women survivors of gender-based violence. Trial registration number ISRCTN58257113 (Registration date: 29 October 2024) Trial sponsor Universitas Padjadjaran, Faculty of Psychology, Jl. Raya Bandung-Sumedang K21, Jatinangor 45363, Indonesia.